EFL LEARNERS’ PERCEPTION ON INTEGRATING E-READING MODULE BASED ECO ELT IN EFL CLASS - Lestari, Iin Widya; Zumrudiana, Ainu; Habibullah, Muhammad Romadlon; Fatoni, Mohammad; Nadiyah, Faridatun (University of Kuningan, 2025)
Environmental issues have emerged widely recognized as global issues in the world. Consequently, they have attracted significant attentions from various academic disciplines, all dedicated preventing further harm to the environment. Upon reflection, it becomes evident that these issues are intrinsically linked to the behavior, awareness, and actions of all communities. Therefore, English Language Teaching (ELT) has a unique opportunity to contribute by providing information and fostering eco-green awareness among learners. To achieve this, a comprehensive research project was undertaken at a university in Bojonegoro to investigate and examine the EFL learners’ perception on implementation of e-reading module based eco-ELT and how EFL learners perceive eco-ELT. This research used mixed method which present and analyze both quantitative and qualitative analysis. The research involved 45 EFL learners, and data was collected through questionnaires and interviews. The questionnaire encompassed various indicators related to the clarity and sustainability of the reading material, presenting reading materials based Eco-ELT themes, and ease of access. The data was analyzed by using data verification, scoring and calculating the percentage of each item and interpret the script of interview. The finding reveals that the majority of the EFL learners have positive perception and acceptance on the use of e-reading module based on eco-ELT in EFL class. The average score was about 50% EFL learners shows their positive perception on the implementation of e-reading module based eco-ELT. While, EFL learners view eco-ELT offers new insights in acquiring information about environment and comprehend reading material while doing the reading exercise. EFL learners imply eco-ELT can encourage them to practice green and sustainable lifestyle to save the earth. Dealing with the findings, eco-ELT can be taken into account as a new innovative approach to develop teaching and learning materials. Consequently, the learners not only acquire the knowledge but also enhance and encourage their characters to love nature.